Influence of the strain rate on the dynamic damage of cement-asphalt mortar in prefabricated slab tracks. (13th September 2021) - Ren, Juanjuan; Ye, Wenlong; Deng, Shijie; Du, Wei; Zhang, Kaiyao
Highlights: The dynamic damage constitutive equation under the strain rate was defined by programming. The in-situ test for different types of actual train loads were carried out. A finite element model considering the damage constitutive relationship of the CA mortar was established. The dynamic damage of cement-asphalt mortar and dynamic response of track structure were analyzed. Abstract: The cement-asphalt mortar (CA mortar), widely adopted in the China railway track system I (CRTS I), is a viscoelastic material whose damage development presents a significant strain rate effect under high-speed loads. The change of the strain rate affects the damage development and consequently influences the force and deformation of track structures. By establishing the dynamic damage constitutive model of the CA mortar under the strain rate effect, we defined the constitutive relationship of the CA mortar by programming and validated it. Under different actual train loads, the dynamic damage law of the CA mortar and how the damage would affect the dynamic response of track structures were discussed in this paper. The result reveals that: I. Under different strain rates, the correlation coefficients between the monotonic compression simulation data and the test data are all above 0.9747; II. When the loading strain is constant, the greater the strain rate, the smaller damage is caused to the mortar; III. The dynamic damage constitutive model under the strain rate effect has only slight effect on the dynamic response of rails and track slabs; IV. The dynamic damage increases with the growth of the initial elastic modulus; V. the dynamic damage would be further aggravated under larger axle loads; VI. With a debonding length from the slab end of 1.5 m, when the debonding height from the slab end increases from 0.5 mm to 1.0 mm, the damage of the mortar under freight train loads increases by two times. Based on the result, this paper deems that the influence of the initial elastic modulus and the debonding height on the dynamic damage of the mortar should be considered during the design and maintenance of track structures, and special attention should be guaranteed when the debonding height exceeds 1.0 mm.